Self-assembly of graphitic carbon nitride nanosheets–carbon nanotube composite for electrochemical simultaneous determination of catechol and hydroquinone - Zhang, Hanqiang; Huang, Yihong; Hu, Shirong; Huang, Qitong; Wei, Chan; Zhang, Wuxiang; Yang, Weize; Dong, Peihui; Hao, Aiyou (Electrochimica acta, 2015)
Schematic diagram of hydrothermal synthesis graphitic carbon nitride nanosheets-carbon nanotube composite and theirs application for electrochemical sensing catechol and hydroquinone. [Display omitted] •Self-assembly of graphitic carbon nitride nanosheets-carbon nanotube composite.•CNNS-CNT show more stronger conductivity than CNNS and CNT.•CNNS-CNT has been performed for detection of catechol and hydroquinone.•The probe was applied to detect practical samples with satisfactory results. In this paper, three-dimensional (3D) graphitic carbon nitride nanosheets-carbon nanotube (CNNS-CNT) composite was synthesized via hydrothermal reaction of 2D CNNS and 1D CNT-COOH by π-π stacking and electrostatic interactions. This CNNS-CNT composite was characterized by transmission electron microscope, scanning electron microscope, x-ray diffraction and fourier-transform infrared. In addition, the CNNS-CNT composite displayed excellent conductivity comparing with CNNS and CNT-COOH monomer. This composite was applied for electrochemical simultaneous determination of catechol (CC) and hydroquinone (HQ) with good sensitivity, wide linear range and low detection limit. In addition, this CNNS-CNT composite modified electrode was also applied to detect practical samples with satisfactory results.